(untitled) (Archives of The Medicine and Case Reports, 2021)
In Indonesia, the cases of cervical cancer are estimated at around 50 per 100.000 people. It was estimatedthattherearemore than 1 millionwomenworldwidewho have cervical cancer, and most of them have not been diagnosed yet or do not have access to screening and medical treatment. P53 codon 72 polymorphism can affect the risk of cervical cancer through the regulation of proliferationandcellapoptosis.The purpose of this research was to investigate the association between p53 codon 72 polymorphism and cases of cervical cancer. This research was observational analytic research. The research was done by examining in the laboratory of Molecular Biology, Faculty of Medicine, Universitas Sriwijaya by using a case-control study approach.Thesampleoftheresearchconsistedof 70 subjects,and they were divided into two groups:35 in case group and 35 in the control group. The determination of genotype and allotype was done by using PCR-RFLP technics. The results of the research showed there was a significant difference between p53 codon 72 polymorphism between the case group and control group. The results of genotypes of p53 codon 72 polymorphism in the case group were seven respondents (20.0%) with Pro/Pro genotype, five respondents (14.3%) with Arg/Arg genotype, and 23 respondents (65.7%) with Pro/Arg. While in control group, there were 28 respondents (80.0%) with Pro/Pro genotype, 0 respondent (0.0%) with Arg/Arg genotype, and 7 respondents (20%) with Pro/Arg. The frequency of the Prolin allele in case group was 37 (52.9%), and the Arginin allele was 33 (47.1%), while the frequency of the Prolin allele in the control group was 63 (90%), and the Arginin allele was 7 (10%). The Chi-Squareofgenotypewas valued0.000,OR1,304andCI95%1,071-5,891,whiletheallelewas valued 0.000, OR 8.027 and CI 95% 3.228-19.962. There was anassociation between genotype and allele of p53 codon 72 polymorphismandcases of cervicalcancer.